2012
DOI: 10.1302/0301-620x.94b3.27407
|View full text |Cite
|
Sign up to set email alerts
|

The early radiological results of the uncemented Oxford medial compartment knee replacement

Abstract: We carried out a prospective investigation into the radiological outcomes of uncemented Oxford medial compartment unicondylar replacement in 220 consecutive patients (231 knees) performed in a single centre with a minimum two-year follow-up. The functional outcomes using the mean Oxford knee score and the mean high-activity arthroplasty score were significantly improved over the pre-operative scores (p < 0.001). There were 196 patients with a two-year radiological examination performed under fluoroscopic guida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 17 publications
(20 reference statements)
2
31
0
Order By: Relevance
“…21 These findings are similar to those of previously published studies of cementless OUKRs in smaller numbers of patients. 10,12 At a mean of 38.2 months (19 to 88) postoperatively, the rate of complications and revision is not significantly different from that in the previously published series of cemented OUKRs, and functional outcomes are equivalent.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…21 These findings are similar to those of previously published studies of cementless OUKRs in smaller numbers of patients. 10,12 At a mean of 38.2 months (19 to 88) postoperatively, the rate of complications and revision is not significantly different from that in the previously published series of cemented OUKRs, and functional outcomes are equivalent.…”
Section: Discussionmentioning
confidence: 74%
“…Femoral radiolucencies were assessed on the lateral radiograph by examining the flat area at the posterior femoral condyle and the area around the femoral pegs. 12 The extent of tibial radiolucencies was assessed using the AP radiograph by dividing the area under the tibial tray into six zones, and radiolucencies were described as partial or complete, depending on whether all six zones were involved (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A low prevalence of radiolucency beneath cementless tibial components has previously been shown. 10 Cementless fixation of a TKA has a chequered history and is not used routinely in most centres, as it is associated with a high rate of revision. [11][12][13] The NJR reported that only 6.7% of all TKAs in England and Wales were cementless, with no differentiation between the types of cementless fixation, and had a significantly greater risk of revision at eight years than cemented TKA.…”
mentioning
confidence: 99%
“…Each surgeon then assessed the radiographs for radiolucency in their own time on computers of their choice; all the computers chosen were office-based systems. The tibial tray was considered to be divided into seven zones, previously defined by Hooper et al [13] (figure 1), and the surgeon recorded whether radiolucency was present or not in each zone. In order to best reproduce the clinical situation, the surgeons were not given any guidance as to how to identify radiolucency within the zones; they were just presented with the radiographs, and a form to complete containing an image illustrating the location of the zones.…”
Section: Manual Assessment Of Radiolucencymentioning
confidence: 99%